Locked Grooves, a Circle of Hands. Paranormal Affects in Georgina Starr’s I am the Medium - Fisher, Jennifer (Revue musicale OICRM, 2023)
This article examines the complex affects of I am the Medium, a vinyl record artwork and sound installation produced by Georgina Starr, a London-based visual artist affiliated with the second wave of Young British Artists (ybas). This project was exhibited at the Le Confort Moderne in Poitiers, France in 2010. Starr’s limited- edition lp features recordings made during séances in which she participated over the period of a year. Formally, the record is extraordinary in that it is structured in the form of locked grooves, rather than the spiral continuum of conventional vinyl recordings. Each discrete track consists of a 1.8 second phrase that repeats, creating a mantra-like incantation that resonates in the gallery atmosphere. Much in the same way that sound vibrations are captured and replayed on vinyl records, the etheric signatures of spirit entities manifest through mediumistic channeling. Issues of mediumship raised by this work will be situated in relation to Starr’s sound oeuvre, particularly her projects that have deployed paranormal methodologies.